Research on Performance of Modern Rural Financial Poverty Alleviation Based on Data Envelopment Method - Zhenwei, Yu; Musah, Adiza Alhassan (Migration Letters, 2023)
Rural poverty alleviation is the mainstream form of poverty alleviation in China. For a long time, the evaluation of the performance of modern rural financial poverty alleviation is relatively lacking. Based on the purpose of the project, this paper evaluates both economic and social aspects, and analyzes the poverty alleviation performance of 12 typical poor villages in Jilin Province, Hunan Province, and Inner Mongolia Autonomous Region from 2016 to 2019 through data envelopment method. According to the results obtained, it is further pointed out that in the rural poverty alleviation work, adjustments and optimizations should be made in terms of carrying out poverty alleviation in characteristic industries and improving the expenditure structure.